Changes in circulating lipids level over time after acquiring HCV infection: results from ERCHIVES. Issue 1 (December 2015) - Butt, Adeel; Yan, Peng; Simon, Tracey; Chung, Raymond; Abou-Samra, Abdul-Badi
Abstract Background Changes in lipid levels over time after acquiring HCV infection, and how they differ from HCV-uninfected persons are unknown. Methods We used ERCHIVES to identify those with a known HCV seroconversion window and persistently negative controls. We excluded subjects with HIV and hepatitis B and those who received lipid lowering agents. Total Cholesterol (TC), low-density lipoproteins (LDL), high-density lipoproteins (HDL), triglycerides (TG) and non-HDL cholesterol were retrieved at yearly intervals and plotted over time. Results Among 1, 270 HCV+ and 5, 070 HCV- subjects, median age [IQR] was 47[37, 53] for HCV+ and 52[47, 57] for the HCV- group; 69 % were White and 91 % were males in each group. Mean BMI [SD] was 26.94[6.73] in the HCV+ and 28.15 [5.98] in the HCV- group (P < 0.001) . Over a 10-year follow-up period among HCV+ persons, TC decreased by (mean (SD) mg/dL) 12.06(36.95), LDL by 9.22(31.44), TG by 13.58(87.01) and non-HDL-C by 12.55(35.14). Among HCV- persons, TC cholesterol decreased by 4.15(31.21), LDL by 4.16(26.51); TG by 4.42(82.34) and non-HDL-C by 5.78(30.17). Conclusions After HCV acquisition, TC, LDL, TG and non-HDL-C progressively decline over time independent of BMI and liver fibrosis. Consequences of lipid changes and the need and optimal timing of lipid lowering therapy in HCV+ persons require further study.